Root microbiota dynamics of perennial Arabis alpina are dependent on soil residence time but independent of flowering time - Dombrowski, Nina; Schlaeppi, Klaus; Agler, Matthew T.; Hacquard, Stephane; Kemen, Eric; Garrido-Oter, Ruben; Wunder, Joerg; Coupland, George; Schulze-Lefert, Paul (NATURE PUBLISHING GROUP, 2017)
Recent field and laboratory experiments with perennial Boechera stricta and annual Arabidopsis thaliana suggest that the root microbiota influences flowering time. Here we examined in long-term time-course experiments the bacterial root microbiota of the arctic-alpine perennial Arabis alpina in natural and controlled environments by 16S rRNA gene profiling. We identified soil type and residence time of plants in soil as major determinants explaining up to 15% of root microbiota variation, whereas environmental conditions and host genotype explain maximally 11% of variation. When grown in the same soil, the root microbiota composition of perennial A. alpina is largely similar to those of its annual relatives A. thaliana and Cardamine hirsuta. Non-flowering wild-type A. alpina and flowering pep1 mutant plants assemble an essentially indistinguishable root microbiota, thereby uncoupling flowering time from plant residence time-dependent microbiota changes. This reveals the robustness of the root microbiota against the onset and perpetual flowering of A. alpina. Together with previous studies, this implies a model in which parts of the root microbiota modulate flowering time, whereas, after microbiota acquisition during vegetative growth, the established root-associated bacterial assemblage is structurally robust to perturbations caused by flowering and drastic changes in plant stature.